2008
DOI: 10.1177/1358863x07087731
|View full text |Cite
|
Sign up to set email alerts
|

Five-year incidence of cardiovascular disease and its predictors in Greece: the ATTICA study

Abstract: The 5-year incidence of cardiovascular disease (CVD) and its determinants, in a sample of men and women from Greece, was evaluated. From May 2001 to December 2002, 1514 men and 1528 women (>18 years old) without any clinical evidence of CVD, living in the Attica area, Greece, were enrolled in the ATTICA study. In 2006, a group of experts performed the 5-year follow-up (941 of the 3042 (31%) participants were lost to follow-up). Development of CVD (coronary heart disease, acute coronary syndromes, stroke, or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
1
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 29 publications
(25 reference statements)
13
75
1
20
Order By: Relevance
“…population (ATTICA study), while the results regarding the prevalence of hypertension are similar to those reported previously (5) . However, the study sample in the THISEAS study is a decade older than the study aforementioned; therefore the results are not totally comparable.…”
Section: Discussionsupporting
confidence: 89%
“…population (ATTICA study), while the results regarding the prevalence of hypertension are similar to those reported previously (5) . However, the study sample in the THISEAS study is a decade older than the study aforementioned; therefore the results are not totally comparable.…”
Section: Discussionsupporting
confidence: 89%
“…A wide body of scientific evidence relates diet and incidence of CVD (33)(34)(35) . There is also increasing scientific evidence that diets high in consumption of fruits, vegetables, legumes and whole grains, which also include fish, nuts and low-fat dairy products, have protective health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that CVD is highest among communities originating in the Middle East and southern European. The Greek population is part of this group, and CVD is a significant concern among them as well as in their nation of origin (Panagiotakos et al, 2008;Allender et al, 2008).…”
Section: Cardiovascular Disease In Australiamentioning
confidence: 99%